Measuring Debt-Profit Relation: Evidence in Energy Sector from Indonesia Stock Exchange - Ardhiani Fadila; M Marlina; Alfida Aziz (Universitas Pendidikan Indonesia, 2024)
This research aims to assess the impact of debt utilization on the performance of companies listed on the Indonesia Stock Exchange during the period of 2012-2021. Panel data analysis is employed to analyze 35 companies operating in the energy sector, includes the use of a fixed effect model, common effect model, and Hausman test to determine the most suitable model for analysing the data. Short-term and long-term debt measurements are used as independent variables to evaluate their effects on company performance based on accounting metrics, including Return on Assets (ROA), Return on Equity (ROE), and Return on Sales (ROS). The findings reveal that both short-term and long-term debt significantly affect company profitability. Additionally, companies in the energy sector predominantly rely on long-term debt for financing. Tangible assets and company size exhibit varying effects on performance. Furthermore, macroeconomic factors, such as exchange rates, play a significant role. These findings are consistent with the